2022
DOI: 10.1007/s11089-021-00995-w
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Children’s Coping with Representation of Death During the COVID-19 Pandemic: Qualitative Research with Parents

Abstract: The coronavirus disease 2019 (COVID-19) pandemic and the related lockdown measures have had intense negative impacts on the psychological well-being of both adults and children. Among such impacts is a significant increase in mortality salience and changes in how people deal with grief and losses. This qualitative research used semi-structured interviews with 23 Italian parents to draw insights on the impact of the pandemic on children aged 5˗15 years with regard to their representation of death and the eventu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…It enhances children’s concentration, provides them with better physiological and psychological coping mechanisms to address the pressures of modern life, and improves their mental health throughout their academic journeys [ 52 ]. Exploring one’s spiritual and transcendent dimensions from an early age not only allows individuals to form their own understanding and representation of death but also empowers children to face challenging moments, such as those caused by the pandemic [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It enhances children’s concentration, provides them with better physiological and psychological coping mechanisms to address the pressures of modern life, and improves their mental health throughout their academic journeys [ 52 ]. Exploring one’s spiritual and transcendent dimensions from an early age not only allows individuals to form their own understanding and representation of death but also empowers children to face challenging moments, such as those caused by the pandemic [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that over the past three years, minors experienced anxiety, depressive symptoms, sleep problems, anger, a lack of peer contact, and concerns about the present and future [ 12 , 17 , 18 ]. Social stimuli were reduced, resulting in boredom and emotional states influenced by the fears and worries of adults regarding contagion, illness, disruptions in work life, anxiety about physically distant loved ones, and the fear of loss [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…La muerte durante la pandemia es un ejemplo de un duelo difícil de elaborar por las características de la enfermedad, la probabilidad de contagio, lo incierto del pronóstico y la dificultad para acompañar a la persona enferma (Ferrer, 2020;Mora-Guevara, 2021). Como lo enuncian Acinas (2021) y Pompele et al (2022), los protocolos de bioseguridad resultaron complejos para los niños, especialmente en los casos de muerte. Además, las restricciones de los rituales funerarios impidieron que las personas se despidieran y acompañaran al difunto a su última morada (Del Castillo & Velazco, 2020;Mora-Guevara, 2021).…”
Section: Elaboración Del Duelo Durante La Pandemiaunclassified
“…Typically, people rely on religion and spirituality to cope with periods of high emotional stress and declining health [32]. Moreover, the spiritual/religious dimension aids in finding meaning amid the most difficult and challenging circumstances [33], such as the traumatic experience of the COVID-19 pandemic [33,34]. In particular, those grieving may find comfort in viewing death as a passage and in maintaining a bond with the departed [35], often managing anger more effectively than those who feel abandoned by a higher power [33].…”
Section: Introductionmentioning
confidence: 99%